Evaluation of urban traffic noise pollution based on noise maps. (October 2020) - Yang, Weijun; He, Jinying; He, Canming; Cai, Ming
Graphical abstract: Highlights: Noise pollution evaluation of a city based on the hourly noise maps. The study area is divided into four types of regions based on land use and requirements for the acoustic environment. The noise pollution analysis is based on a grid of noise receiving points with a step length of 8 m. Abstract: Traffic noise pollution has become a major environmental issue that plagues urban residents. The purpose of this study is to evaluate the traffic noise pollution based on noise maps. Twenty-four-hour noise maps of the Chancheng District in Foshan, China were developed for this study, and the results analyzed. The study area is divided into four types, based on the land use requirements for the acoustic environment, and the calculated noise value is compared to the noise limits of each class of the area. The average equivalent sound pressure level of the entire study area indicates the noise pollution is modest, but further analysis of the noise data in various types of areas shows a high magnitude of noise and long-lasting noise pollution near street-front buildings as well as the areas where quietness is required. It was also found that the noise level of the city is higher during off-peak hours than during rush hours, probably due to the faster speed and larger traffic volume during the off-peak hours. It is urgent to develop effective noise reduction measures to mitigate traffic noise pollution at night, based on the evaluation results.